Rancang Bangun Sistem Lampu Tangga Otomatis Berbasis Arduino Mega 2560 Menggunakan Sensor Inframerah dan Notifikasi Audio - Iswidodo Iswidodo; Sri Mumpuni Ngesti Rahaju; Raka Uta Gumelar (Universitas Dirgantara Marsekal Suryadarma, 2026)
This study aims to design and evaluate an automatic stair lighting system based on the Arduino Mega 2560 microcontroller utilizing infrared sensors to detect user movement on ascending and descending stairways. The system is equipped with LED lights, an audio module, and an LCD to display operational status and provide warnings when users take the wrong stair path. The research method employs a prototype approach consisting of hardware design, software development, system integration, and functional testing. The tests were conducted on sensor detection performance, lighting activation response, audio notification, LCD display performance, and system operation in both manual and automatic modes. The results show that the infrared sensors are able to distinguish detected and undetected object conditions based on changes in output voltage levels, enabling the lights to turn on according to user movement on active steps. The system is also capable of generating voice warnings for incorrect path usage and displaying real-time system information. In general, the developed prototype operates according to the intended design and has the potential to improve safety, convenience, and lighting efficiency in stair areas.